PENGGUNAAN MEDIA SOSIAL SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR MAHASISWA - Sari, Yolanda Intan; Elida, Elida (Ensiklopedia Education Review, 2024)
-Abstract: The purpose of writing this article is to analyze the use of social media as a learning medium to increase student learning motivation using the literature study method. The research results show that the use of social media as a learning medium can increase student learning motivation. Social media is used to facilitate communication, increase motivation and access materials that students cannot access.Keywords: Social Media, Learning Media, Learning Motivation.